HUBUNGAN KETERSEDIAAN PANGAN DAN ASUPAN ZAT GIZI DENGAN KADAR HEMOGLOBIN SANTRIWATI SAAT PUASA RAMADHAN (Studi di Pondok Pesantren Al Isti’anah Desa Plangitan Kabupaten Pati Tahun 2017) - Qusna Nur Anisa; Laksmi Widajanti; Martha Irene Kartasurya (Jurnal Kesehatan Masyarakat (Undip), 2017)
Adolescent female students who live in islamic boarding schoolha a high risk for anemia since the nutrient intake is low and experience a fast growing period. One of the factors that can cause low nutrient intake was a fasting period during Ramadhan. Nutrient intake is influenced by food availability at the boarding school. The objective of this study was to analyze the correlation of food availability and nutrient intake on hemmoglobin level of female students during Ramadhan fasting on Islamic boarding school. The research used quantitative method with a cross sectional design. The population of this research were 48 female studentson their 8th grade. They aged between 13 - 15 years old. The subjects were 43 female students who were fastingand fulfill the inclusion criteria. Data were taken by interviews using food recall 2 x 24 hours method, anthropometric measuring and hemoglobin levels measuring using hemocue® Hb 201+ analyzer.data were analysed using Rank Spearman test. The finding showed that 62.8% of the subject were anemic. The food availability levels was low based on Desirable Dietary Pattern (DDP Score) which was 81.23. the energy adequacy levels was low in 86.0% subjects, 46.5% low in protein adequacy levels, 67.4% low in iron adequacy levels, and 60.5% low in vitamin C adequacy levels. There were correlations between energy adequacy levels (p=0.000), protein adequacy levels (p=0.000), iron adequacy levels (p=0.000) and vitamin C adequacy levels (p=0.000) with the hemoglobin level. It is suggested to the organizer to select affordable price foods but still can fulfill the female students need.